Credibility without rules? : monetary framework in the post-Bretton Woods era - Cottarelli, Carlo (IMF WashingtonUS, 1997)
Provides a chronicle of the evolution of the theory and practice of monetary policy during the last 25 years. Focuses on monetary frameworks, that is, on the announced basic principles and institutional rules guiding the execution of monetary policy.